Cooperative relaying in hybrid-integrated satellite-terrestrial system - Iqbal, Arif; Ahmed, Kazi Mohiuddin; Poompat Saengudomlert; Tripathi, Nitin Kumar; Higher Education Commission (HEC), Pakistan; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
In this dissertation, a hybrid/integrated satellite-terrestrial system with AF (amplify- and-forward) cooperative diversity scheme using single, multiple and MIMO (multiple input and multiple output) enabled fixed relay node has been investigated. High data rate satellite services to mobile and especially indoor users can be provided by using cooperative fixed terrestrial relay nodes. The performance measure parameters of the proposed systems are the outage probability, symbol error rate (SER) and ergodic ca- pacity. The mathematical analysis has been carried out on non independent and identi- cally distributed (non-iid) shadowed Rician, Rician, Rayleigh, and Nakagami-m fading distributions. Real satellite channel parameters have been taken from the literature for modeling a number of shadowing conditions from deep shadowed to a light shadowed satellite link to make our analysis closer to a practical system. From the literature review, it is found that the outage probability, SER and ergodic capacity closed-form mathematical expressions have not been derived for a hybrid/integrated satellite ter- restrial cooperative system under non-iid channels. To assist performance measuring parameters, we have formulated closed-form analytical expressions of probability den- sity function (PDF), cumulative distribution function (CDF) and moment generating function (MGF). A MGF-based method is used to evaluate the SER and outage prob- ability performance of the dual-hop and multi-hop system. Moreover, PDF and CDF- based approach is also developed to derive SER and outage probability closed-form expressions for the relaying path. Furthermore, we have formulated an approximate expression of the ergodic capacity for a multi-hop hybrid satellite-terrestrial system. We have further investigated a dual-hop MIMO enabled relay hybrid satellite- terrestrial system. The impact of the fixed-relay node with various receiving and transmitting antenna on the performance of a hybrid satellite-terrestrial system has been researched. An analytical approach is derived to examine the system perfor- mance in terms of outage probability, SER and ergodic capacity. vVe have derived mathematical expressions for PDF, CDF, MGF and SER of the bounded end-to-end SNR. An approximate ergodic capacity expression of the system is also found, which reflects the capacity of the system with MIMO relay node. The performance of the system is evaluated using various antenna configurations at the relay node such as, SIMO (single input multiple output), MISO (multiple input single output), SISO (sin- gle input single output), and MIMO. Our results found that the diversity of the system can be determined by the shadowing effects between the satellite-relay channel as well as, the number of receiving and transmitting antennas at the relay node. The analysis of the study is verified using the results of the numerical computation and Matlab simulation. Finally, we have compared the performance of a multi-hop, and dual-hop MItvl0 enabled relay systems. The results show that the hybrid satellite-terrestrial system with MIMO enabled relay is generating the same SER and outage curves as the multi- hop system. Moreover, ergodic capacity of the MIMO relay system increases as the number of transmitting and receiving antennas at the relay node increases. Thus, the main limitation of bandwidth degradation in cooperative relaying can be improved by using MIM 0 enable relay node.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Telecommunications, School of Engineering and Technology
Thesis (Ph.D.) - Asian Institute of Technology, 2012
Keywords: Artificial satellites in telecommunication; MIMO systems; Radio relay systems